The predictivity of serum biochemical markers in acute biliary pancreatitis (Nepal Medical College Journal, 2023)
Acute pancreatitis (AP) is the most common gastrointestinal disease requiring hospital admission. Among the etiology of AP gallstones (45%) and alcohol abuse (20%) are the most frequent causes of AP. Sixty-nine patients of AP who met the inclusion criteria were evaluated from July 2021- June 2022. The predictivity of serum biochemical marker alanine transaminase (ALT) in acute biliary pancreatitis and the mean serum biochemical markers (ALT, aspartate transaminase, alkaline phosphatase, bilirubin, amylase and lipase level) in AP were evaluated. Total 69 patients with the diagnosis of AP were included. Forty-six (66.7%) were male and twenty-three (33.3%) were female out of which 12 (17.3%) were diagnosed as biliary pancreatitis and 57 (82.7%) had non-biliary pancreatitis. In non-biliary pancreatitis there were 41 male and 16 females. Non-biliary pancreatitis was more common in male and biliary pancreatitis was more common in female. There was no significant difference in mean levels of amylase in biliary and non-biliary pancreatitis (i.e. in non-biliary pancreatitis; mean ± SD = 387.14 ± 419.53, in biliary pancreatitis mean ± SD = 535.5 ± 533.51, p-value= 0.235 >0.05), the mean lipase was not significantly different in biliary and non-biliary pancreatitis (i.e.in non biliary pancreatitis; mean ± SD=1287.75±894.37, in biliary pancreatitis mean ± SD =1666.41 ± 1150.47, p-value =0.289 > 0.05). There was a significant difference seen among the mean levels of all other parameters (Bilirubin T&D, ALT, AST and ALP) the mean was found to be significant in biliary and non-biliary pancreatitis (i.e. p-value=0.000